BENTUK PENILAIAN PEMBELAJARAN SOSIOLOGI PADA PELAKSANAAN KURIKULUM MERDEKA DI SMAN 5 PADANG - Thaariq Munir (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
The problem in this research starts with the evaluation process, or assessment of the implementation of the independent curriculum. Not many teachers understand the problem of evaluation or assessment by teachers of existing processes. So that the assessment carried out is still unclear. The research objective is a form of sociology learning assessment in the implementation of the independent curriculum. In addition, the theory used is constructivism, namely Lev Vygotsky's theory. This research was conducted with a qualitative approach. The selection of informants using purposive sampling technique with a total of 4 informants. The types of data used in this research are primary data and secondary data. Data collection methods used are observation, in-depth interviews and document studies. Meanwhile the data analysis unit used by the group with Milles Huberman's data analysis is data aggregation, data reduction, data presentation, and drawing conclusions. The results of this study indicate that formative and summative evaluations are used in the assessment of sociology learning at SMA Negeri 5 Padang. Formative evaluation is carried out at the beginning of learning or at the end of learning in the form of feedback. Summative assessment is carried out on material that has been completed which is also called final semester examination. Management of the results of the assessment consists of a) managing the results of the assessment in one learning objective b) managing the learning outcomes at the end of the semester with reporting of learning outcomes.